FRI0173 Role of Methotrexate as Combination Therapy with Adalimumab and Etanercept in Rheumatoid Arthritis: Retrospective Analysis from A Local Registry. (15th July 2016) - Favalli, E.G.; Becciolini, A.; Biggioggero, M.; Crotti, C.; Ughi, N.; Penatti, A.E.; Marchesoni, A.; Meroni, P.L.
Abstract : Background: The role of methotrexate (MTX) in association with TNF inhibitors (TNFi) for the treatment of rheumatoid arthritis (RA) is well defined, although the optimal MTX dose is still unclear. Recently the CONCERTO randomized controlled trial demonstrated efficacy and safety of ascending MTX doses in combination with adalimumab (ADA) for the treatment of MTX-naïve RA [1], but observational data from real-life registries are still lacking. Objectives: The aim of our study is to retrospectively evaluate the effect of different MTX regimen as combination therapy with 1st line ADA and etanercept (ETN) on 6- and 12-month clinical response and safety profile in RA patients. Methods: We selected all RA patients treated with ADA or ETN as 1st line biotherapy in our Rheumatology Department from January 2000 to October 2015. The analysis was performed only on subjects with at least 1-year follow-up and the study population was stratified according to concomitant MTX regimen in 3 subgroups: TNFi as monotherapy (group 1), TNFi in association with low MTX dose (≤10 mg/week, group 2), and TNFi combined with high MTX dose (≥12.5 mg/week, group 3). Six- and 12-month clinical response was evaluated as mean change from baseline of disease activity score 28 (DAS28) and as DAS28 remission/low disease activity (LDA) rates, comparing the 3 subgroups by Kruskal-Wallis and Dunn tests. Results: The study population included 322 RA patients (265 [82.3%] female, mean age [± standard deviation] 55.4 [±12.8] years, disease duration 11.4 [±9.4] years, positive rheumatoid factor 248 [77%], mean baseline DAS28 5.39 [±1.18]) treated with ADA (n=166) or ETN (n=156). According to concomitant MTX regimen, 108 patients were assigned to subgroup 1, 110 to subgroup 2, and 104 to subgroup 3. No significant differences were found in baseline characteristics among the 3 subgroups. The mean change from baseline of DAS28 was significantly higher in subgroup 3 compared with subgroup 1 and 2 at both 6 (2.14, 1.2, and 1.44, respectively; p<0.0001) and 12 months (2.33, 1.26, and 1.46, respectively; p<0.0001). Similarly, in the subgroup 3 we found a significantly higher proportion of patients achieving 1-year remission (44.1, 23.1, and 24.1%, respectively; p<0.0001) or LDA (57.3, 31.7, and 36.1%, respectively; p<0.0001). Treatment withdrawals due to adverse events were significantly more frequent in both subgroup 1 and 2 compared with subgroup 3 (19.3, 16.5, and 9.2%, respectively; p=0.02). Conclusions: Our retrospective analysis demonstrated that in a real life setting the 6- and 12-month clinical response of ADA and ETN was significantly improved by combination strategy only when MTX has been used at high doses (≥12.5 mg/week). Interestingly, increasing MTX dose was also associated with a more favorable safety profile. References: Burmester GR, Kivitz AJ, Kupper H, et al. Efficacy and safety of ascending methotrexate dose in combination with adalimumab: the randomized CONCERTO trial. Ann Rheum Dis 2015;74(6):1037–44. Disclosure of Interest: None declared